Everyday life reflected in the Ukrainian SSR railway press during the Holodomor (1932-1933) - Tetiana Soproniuk (Historijski pogledi)
In this article, the author studied how the local printed media of the South-Western Railways (Ukrainian SSR) reacted to the Holodomor – the artificial famine of 1932–1933. While Soviet newspapers were primarily viewed as instruments for disseminating state-approved narratives, this study argues that the local railway press serves as a valuable but often overlooked source for understanding the multifaceted realities of Soviet society during this tumultuous period. Examining the editorial mechanisms of the railway press, the article discusses the involvement of workers and farmers as correspondents. The use of „robsilkors” (workers’ and farmers’ correspondents) in reporting everyday issues and problems within the railway system highlights a dynamic interaction between the press, its readership, and the authorities. The press functioned as an information conduit to party units and law enforcement, emphasizing the so-called „self-criticism campaigns” and denunciations. Under totalitarian censorship and government control, the newspapers did not openly write about starvation and mass mortality. The press, however, inadvertently provided glimpses into the harsh realities of everyday life, especially in local publications where censorship was comparatively weaker. They unveiled details showcasing the impact of food shortages, malnutrition, and unsanitary conditions. While workers had access to canteens and a food supply system, theft and misappropriation were survival strategies. The press documented cases of intentional damage to grain cargoes and corruption in the food stamps system. Despite receiving state-provided goods, workers faced challenges with the quality of provisions and sanitary conditions in canteens. Moreover, along with covering the famine, the press actively disseminated propaganda aimed at reinforcing the divide between the working class and farmers. This contrast was evident, yet many railway workers experienced life similar to farmers, owning land and resisting state-imposed agricultural policies. The newspapers called on the railway employees to participate in the so-called „mass campaigns” in the villages, which sometimes appeared to be confiscating food from the farmers' houses. Refusal to join these campaigns could lead to the denunciation on the newspapers pages. In conclusion, this research offers a comprehensive understanding of the Soviet railway press during the Holodomor years, revealing its dual nature as a propagandistic tool and a subtle source of authentic information. By dissecting the content and contextualizing the narratives within the socio-political landscape, the study contributes to a more nuanced understanding of the complexities of Soviet society during a period of historical upheaval.